A loxoprofen sodium gel patch and preparation method thereof
Through specific raw material composition and ratio, loxoprofen sodium gel paste was prepared, which solved the problems of poor percutaneous permeability of existing patches and unstable product quality, achieving higher drug utilization and better anti-inflammatory and analgesic effects.
Patent Information
- Application Number
- CN202411737683.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The existing loxoprofen sodium patch has poor permeability, low utilization of drug active ingredients, and poor compatibility of raw material components, resulting in unstable product quality.
Using specific raw material composition and ratios, loxoprofen sodium gel paste is prepared, including the use of a mixture of lecithin and polyethylene glycol-12-hydroxystearate as surfactant, vitamin E and ascorbyl palmitate as antioxidants, and triethanolamine is added to improve product stability.
It significantly improves the release degree and transdermal absorption effect of loxoprofen sodium gel paste, enhances the anti-inflammatory and analgesic effects, and improves the stability and quality consistency of the product.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention belongs to the field of pharmaceutical preparations, and particularly relates to a loxoprofen sodium gel patch and a preparation method thereof. Background Art
[0002] Loxoprofen sodium, chemically named 2-[4-[(2-oxocyclopentyl)methyl]phenyl]propionate sodium dihydrate, is an important 2-phenylpropionic acid non-steroidal analgesic and anti-inflammatory drug, widely used for analgesia and anti-inflammatory treatment of rheumatoid arthritis, low back pain, frozen shoulder, cervical shoulder and wrist syndrome and acute upper respiratory tract inflammation, etc. It is characterized by strong analgesic effect, rapid onset and few adverse reactions. The structure of loxoprofen sodium is as follows:
[0003] .
[0004] As a non-steroidal anti-inflammatory drug, loxoprofen sodium has some side effects. Long-term use can easily cause gastrointestinal irritation and even ulcers. In addition, oral administration will increase the systemic exposure of the drug, further increasing the risk of toxic and side effects. Therefore, it is particularly necessary to reduce the systemic exposure of the drug, reduce the occurrence of drug side effects, and increase the drug concentration in the diseased area. Transdermal drug preparations act directly on the diseased area without passing through the digestive tract and liver, which will greatly reduce the systemic exposure of the drug and reduce the occurrence of toxic and side effects. It is the most suitable dosage form for loxoprofen sodium.
[0005] Chinese invention patent application CN107951866A discloses a loxoprofen sodium patch, comprising a paste coated on a support layer, wherein the paste comprises the following components: loxoprofen sodium, diethanolamine, propylene glycol, azone, menthol, Tween-80, ascorbic acid, micro-powder silica gel, alumina powder, and a matrix prepared with an emulsion-type polyacrylate pressure-sensitive adhesive. The patch provided by the invention exhibits low irritation, and by optimizing the prescription, reduces the incidence of side effects in patients with delayed hypersensitivity and improves the compliance of the preparation. However, it is found during use that the transdermal permeability of the patch is poor, and the utilization rate of the active ingredient of the drug is low, which limits the application of the drug patch in transdermal delivery; and the compatibility between the raw material components is poor, resulting in unstable product quality and difficulty in meeting market demand.
[0006] Compared with creams, patches, traditional rubber plasters, black plasters, etc., gel patches have the following advantages: 1. Easy to administer, suitable for patients who have difficulty taking the drug orally or by injection; 2. The drug enters the systemic circulation directly after percutaneous absorption, avoiding the destructive effects of the gastrointestinal tract on the drug and the first-pass effect of the liver; 3. Long duration of action and stable blood drug concentration, avoiding the phenomenon of excessive peak drug concentration and excessively low concentration; 4. Large drug loading capacity, compared with patches, reduces the number of dosing times and does not contaminate clothing; 5. Improves the safety of drug treatment, and if side effects are found, it is easy to stop the administration immediately.
[0007] Chinese invention patent application CN101416955A discloses a loxoprofen sodium cataplasm with an improved cataplasm matrix, wherein the cataplasm matrix adopts two or more cross-linking agents in combination to achieve the purpose of increasing the viscosity of the paste, improving the ductility and formability of the paste. The cataplasm matrix excipients include: 20-50 parts of glycerol, 1-3 parts of azone, 10-5 parts of polyethylene glycol 400, 0.3-1.5 parts of titanium dioxide, 2-7 parts of skeleton material, 1-3 parts of gelatin, 0.5-1 parts of cross-linked povidone XL-10, 0.02-11 parts of combined cross-linking agent, 0.1-1 parts of peppermint oil, 1-3 parts of sodium carboxymethyl cellulose, 0.02-0.05 parts of disodium ethylenediaminetetraacetic acid, 0.5-1.0 parts of tartaric acid, 0.1-0.4 parts of methyl paraben, 16-201 parts of deionized water, preferably 30-75 parts. However, this invention uses azone as a transdermal penetration enhancer, which poses a risk of the drug entering the general circulation and causing systemic adverse reactions. Summary of the invention
[0008] In view of the deficiencies in the prior art, the present invention provides a loxoprofen sodium gel patch and a preparation method thereof.
[0009] In order to achieve the above-mentioned purpose of the present invention, the specific technical solution adopted by the present invention is:
[0010] A loxoprofen sodium gel patch, comprising a backing layer, a drug storage layer and a protective layer from top to bottom;
[0011] The raw materials of the drug storage layer include: loxoprofen sodium emulsion, gel matrix and pH regulator;
[0012] The raw materials of the gel matrix include, by weight: 20-30 parts of sodium polyacrylate, 5-10 parts of acrylic acid grafted starch 300, 0.5-1 parts of triethanolamine, 15-20 parts of gelatin, 0.5-5 parts of sodium edetate, 0.5-2.5 parts of a cross-linking agent, 1-5 parts of a filler, 25-35 parts of a moisturizer, 0.05-1 parts of an antibacterial agent, 0.005-1 parts of an antioxidant, and 40-50 parts of water;
[0013] The antioxidant is a mixture of vitamin E and palmitate ascorbyl;
[0014] The surfactant is a mixture of lecithin and polyethylene glycol-12-hydroxystearate.
[0015] Preferably, the mass ratio of vitamin E to palmitol ascorbyl in the antioxidant is 1:1; the mass ratio of lecithin to polyethylene glycol-12-hydroxystearate in the surfactant is 1:1-2.
[0016] Preferably, the crosslinking agent is selected from one or more of aluminum hydroxide, aluminum chloride, aluminum citrate, potassium aluminum sulfate and aluminum glycolate; the filler is selected from one or two of silicon dioxide, talc, titanium dioxide, kaolin and zinc oxide.
[0017] Preferably, the moisturizer is a mixture of sorbitol, hyaluronic acid and polyethylene glycol; the antibacterial agent is selected from at least one of glyceryl monostearate, glyceryl monolaurate, glyceryl monooleate, methyl parahydroxybenzoate, propyl parahydroxybenzoate, sorbic acid and benzoic acid.
[0018] Preferably, the raw materials of the loxoprofen sodium emulsion include, by weight: 0.5-2 parts of loxoprofen sodium, 1-2 parts of a surfactant, 3-8 parts of an organic solvent and 6-8 parts of water.
[0019] Preferably, the organic solvent is a mixture of caprylic glyceride and diethyl adipate.
[0020] Preferably, the pH adjuster is one or two of L-tartaric acid, citric acid and phosphoric acid.
[0021] Preferably, the mass ratio of the loxoprofen sodium emulsion to the gel matrix is 1:5-8.
[0022] The present invention also relates to a method for preparing the loxoprofen sodium gel patch, comprising the following steps:
[0023] (1) preparing loxoprofen sodium emulsion;
[0024] (2) uniformly mixing all the raw materials in the gel matrix to obtain a gel matrix;
[0025] (3) adding the loxoprofen sodium emulsion to the gel matrix, mixing thoroughly, and then adding a pH adjuster to adjust the pH to 5.0-6.0 to obtain a drug-containing ointment;
[0026] (4) The drug-containing ointment is evenly applied onto the backing layer to obtain a loxoprofen sodium gel patch.
[0027] The invention also relates to the application of the loxoprofen sodium gel patch in the preparation of analgesic and anti-inflammatory drugs.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The present invention selects a specific raw material composition and ratio, and the prepared loxoprofen sodium gel patch has a significant release rate and transdermal absorption effect. The mixture of lecithin and polyethylene glycol-12-hydroxystearate is selected as a surfactant, which can not only stabilize the release of loxoprofen sodium, but also facilitate the transdermal absorption effect, thereby achieving a better anti-inflammatory and analgesic effect.
[0030] (2) In the present invention, vitamin E and palmitate ascorbyl are selected as antioxidants together, and triethanolamine is added, which can effectively synergistically inhibit the formation of impurities and improve product stability. DETAILED DESCRIPTION
[0031] The present invention will be further described in detail below in conjunction with specific examples. The following examples are not intended to limit the present invention, but are only intended to illustrate the present invention. The experimental methods used in the following examples are generally conventional, unless otherwise specified, and the materials, reagents, etc. used in the following examples are commercially available, unless otherwise specified.
[0032] Example 1
[0033] A loxoprofen sodium gel patch comprises, from top to bottom, a backing layer, a drug storage layer and a protective layer; wherein the raw materials of the drug storage layer are: loxoprofen sodium emulsion, gel matrix and pH regulator (citric acid).
[0034] The raw materials of the gel matrix are, by weight, 25 parts of sodium polyacrylate, 8 parts of acrylic acid grafted starch 300, 0.6 parts of triethanolamine, 18 parts of gelatin, 2 parts of sodium edetate, 1.5 parts of aluminum hydroxide, 3 parts of silicon dioxide, 30 parts of moisturizer (sorbitol, hyaluronic acid and polyethylene glycol in a mass ratio of 1:0.5:1), 0.5 parts of methyl parahydroxybenzoate, 0.1 parts of antioxidant (vitamin E and ascorbyl palmitate in a mass ratio of 1:1) and 45 parts of water.
[0035] The raw materials of the loxoprofen sodium emulsion are, by weight, 1.5 parts of loxoprofen sodium, 1.5 parts of a surfactant (lecithin and polyethylene glycol-12-hydroxystearate in a mass ratio of 1:1.5), 5 parts of diethyl adipate and 7 parts of water.
[0036] The preparation method of the above loxoprofen sodium gel patch is:
[0037] (1) Preparing loxoprofen sodium emulsion: dissolving loxoprofen sodium in water, adding a surfactant and diethyl adipate, and mixing well to obtain loxoprofen sodium emulsion;
[0038] (2) uniformly mixing all the raw materials in the gel matrix to obtain a gel matrix;
[0039] (3) adding the loxoprofen sodium emulsion to the gel matrix in a mass ratio of 1:6, and after thorough mixing, adding citric acid to adjust the pH to 5.5 to obtain a drug-containing ointment;
[0040] (4) The drug-containing ointment is evenly applied onto the backing layer to obtain a loxoprofen sodium gel patch.
[0041] Example 2
[0042] A loxoprofen sodium gel patch comprises, from top to bottom, a backing layer, a drug storage layer and a protective layer; wherein the raw materials of the drug storage layer are: loxoprofen sodium emulsion, gel matrix and pH regulator (citric acid).
[0043] The raw materials of the gel matrix are, by weight, 30 parts of sodium polyacrylate, 10 parts of acrylic acid grafted starch 300, 1 part of triethanolamine, 20 parts of gelatin, 5 parts of sodium edetate, 2.5 parts of aluminum hydroxide, 5 parts of silicon dioxide, 35 parts of moisturizer (sorbitol, hyaluronic acid and polyethylene glycol in a mass ratio of 1:1:1), 1 part of methyl parahydroxybenzoate, 1 part of antioxidant (vitamin E and ascorbyl palmitate in a mass ratio of 1:1) and 50 parts of water.
[0044] The raw materials of the loxoprofen sodium emulsion are, by weight, 2 parts of loxoprofen sodium, 2 parts of a surfactant (lecithin and polyethylene glycol-12-hydroxystearate in a mass ratio of 1:1), 8 parts of diethyl adipate and 8 parts of water.
[0045] The preparation method of the above loxoprofen sodium gel patch is:
[0046] (1) Preparing loxoprofen sodium emulsion: dissolving loxoprofen sodium in water, adding a surfactant and diethyl adipate, and mixing well to obtain loxoprofen sodium emulsion;
[0047] (2) uniformly mixing all the raw materials in the gel matrix to obtain a gel matrix;
[0048] (3) adding the loxoprofen sodium emulsion to the gel matrix in a mass ratio of 1:8, and after thorough mixing, adding citric acid to adjust the pH to 6.0 to obtain a drug-containing ointment;
[0049] (4) The drug-containing ointment is evenly applied onto the backing layer to obtain a loxoprofen sodium gel patch.
[0050] Example 3
[0051] A loxoprofen sodium gel patch comprises, from top to bottom, a backing layer, a drug storage layer and a protective layer; wherein the raw materials of the drug storage layer are: loxoprofen sodium emulsion, gel matrix and pH regulator (L-tartaric acid).
[0052] The raw materials of the gel matrix are, by weight, 20 parts of sodium polyacrylate, 5 parts of acrylic acid grafted starch 300, 0.5 parts of triethanolamine, 15 parts of gelatin, 0.5 parts of sodium edetate, 0.5 parts of aluminum hydroxide, 1 part of silicon dioxide, 25 parts of moisturizer (sorbitol, hyaluronic acid and polyethylene glycol in a mass ratio of 1:0.5:1), 0.05 parts of methyl parahydroxybenzoate, 0.005 parts of antioxidant (vitamin E and ascorbyl palmitate in a mass ratio of 1:1) and 40 parts of water.
[0053] The raw materials of the loxoprofen sodium emulsion are, by weight, 0.5 parts of loxoprofen sodium, 1 part of a surfactant (lecithin and polyethylene glycol-12-hydroxystearate in a mass ratio of 1:1.5), 3 parts of diethyl adipate and 6 parts of water.
[0054] The preparation method of the above loxoprofen sodium gel patch is:
[0055] (1) Preparing a loxoprofen sodium emulsion: dissolving loxoprofen sodium in water, adding a surfactant and an organic solvent, and mixing them uniformly to obtain a loxoprofen sodium emulsion;
[0056] (2) uniformly mixing all the raw materials in the gel matrix to obtain a gel matrix;
[0057] (3) adding the loxoprofen sodium emulsion to the gel matrix in a mass ratio of 1:5, and after thorough mixing, adding citric acid to adjust the pH to 5.5 to obtain a drug-containing ointment;
[0058] (4) The drug-containing ointment is evenly applied onto the backing layer to obtain a loxoprofen sodium gel patch.
[0059] Example 4
[0060] A loxoprofen sodium gel patch comprises, from top to bottom, a backing layer, a drug storage layer and a protective layer; wherein the raw materials of the drug storage layer are: loxoprofen sodium emulsion, gel matrix and pH regulator (L-tartaric acid).
[0061] The raw materials of the gel matrix are as follows, by weight: 25 parts of sodium polyacrylate, 5 parts of acrylic acid grafted starch 300, 0.5 parts of triethanolamine, 20 parts of gelatin, 1 part of sodium edetate, 1 part of aluminum hydroxide, 3 parts of silicon dioxide, 25 parts of moisturizer (sorbitol, hyaluronic acid and polyethylene glycol in a mass ratio of 1:0.5:1), 0.1 parts of methyl parahydroxybenzoate, 0.5 parts of antioxidant (vitamin E and palmitate ascorbyl in a mass ratio of 1:1), and 50 parts of water.
[0062] The raw materials of the loxoprofen sodium emulsion are, by weight, 1 part of loxoprofen sodium, 1.5 parts of a surfactant (lecithin and polyethylene glycol-12-hydroxystearate in a mass ratio of 1:2), 6 parts of diethyl adipate and 8 parts of water.
[0063] The preparation method of the above loxoprofen sodium gel patch is:
[0064] (1) Preparing loxoprofen sodium emulsion: dissolving loxoprofen sodium in water, adding a surfactant and diethyl adipate, and mixing well to obtain loxoprofen sodium emulsion;
[0065] (2) uniformly mixing all the raw materials in the gel matrix to obtain a gel matrix;
[0066] (3) adding the loxoprofen sodium emulsion to the gel matrix in a mass ratio of 1:6, and after thorough mixing, adding citric acid to adjust the pH to 6.0 to obtain a drug-containing ointment;
[0067] (4) The drug-containing ointment is evenly applied onto the backing layer to obtain a loxoprofen sodium gel patch.
[0068] Comparative Example 1
[0069] The difference between this comparative example and Example 1 is that the surfactant in the raw material of the loxoprofen sodium emulsion is only lecithin.
[0070] Comparative Example 2
[0071] The difference between this comparative example and Example 1 is that the surfactant in the raw materials of the loxoprofen sodium emulsion is only polyethylene glycol-12-hydroxystearate.
[0072] Comparative Example 3
[0073] The difference between this comparative example and Example 1 is that the antioxidant in the raw materials of the gel matrix is only vitamin E.
[0074] Comparative Example 4
[0075] The difference between this comparative example and Example 1 is that the antioxidant in the raw material of the gel matrix is only ascorbyl palmitate.
[0076] Comparative Example 5
[0077] The difference between this comparative example and Example 1 is that the acrylic acid grafted starch 300 in the gel matrix is replaced by methyl acrylate-2-ethylhexyl acrylate copolymer resin emulsion (purchased from Beijing Yihui Dongfang Trading Co., Ltd.).
[0078] Comparative Example 6
[0079] The only difference between this comparative example and Example 1 is that no triethanolamine is added to the gel matrix.
[0080] Comparative Example 7
[0081] The difference between this comparative example and Example 1 is that the raw material ratio of the gel matrix is different, which is as follows:
[0082] The raw materials of the gel matrix are, by weight, 40 parts of sodium polyacrylate, 5 parts of acrylic acid grafted starch 300, 0.3 parts of triethanolamine, 10 parts of gelatin, 2 parts of sodium edetate, 1.5 parts of aluminum hydroxide, 8 parts of silicon dioxide, 25 parts of moisturizer (sorbitol, hyaluronic acid and polyethylene glycol in a mass ratio of 1:0.5-1:1), 0.02 parts of methyl parahydroxybenzoate, 1.5 parts of antioxidant (vitamin E and ascorbyl palmitate in a mass ratio of 1:1) and 50 parts of water.
[0083] Comparative Example 8
[0084] The difference between this comparative example and Example 1 is that the preparation method is different, which is as follows:
[0085] (1) directly mixing the raw materials of loxoprofen sodium emulsion and the raw materials of gel matrix, and after fully mixing, adding citric acid regulator to adjust the pH to 5.5 to obtain a drug-containing ointment;
[0086] (2) The drug-containing ointment is evenly applied onto the backing layer to obtain a loxoprofen sodium gel patch.
[0087] Effect test
[0088] Test Example 1 Sensory Evaluation
[0089] The samples of Examples 1-4 were applied to the wrists of 30 volunteers in each group, and the film residue, skin follow-up, use comfort, skin irritation, skin allergy, and peeling pain were evaluated. The results are shown in Table 1.
[0090] Table 1 Evaluation results
[0091]
[0092] According to Table 1, the loxoprofen sodium gel patches prepared in Examples 1-4 had good sensory evaluations, and had excellent evaluation results in terms of film residue, skin followability, comfort in use, skin irritation, skin allergy, and pain in peeling.
[0093] Test Example 2 Release Test
[0094] The modified Franz diffusion cell method was used, with Jinlong cellulose acetate membrane as a barrier, and the loxoprofen sodium gel patches prepared in Examples 1-3 and Comparative Examples 1-8 were used to conduct an in vitro release test. The determination method is as follows:
[0095] Using phosphate buffer as the release medium, the cut Jinlong cellulose acetate membrane has a radius of 0.7 cm and an area of 1.54 cm 2 The water bath temperature was adjusted to be constant at (32±0.5)℃, the stirring speed was 500rpm, 4ml of release medium was drawn at 1h, 2h, 4h, 6h, 8h, 12h, and 24h, and an equal amount of (32±0.5)℃ phosphate buffer was added at the same time. The cumulative release percentage (i.e., the percentage of the cumulative permeated loxoprofen sodium to the total amount of loxoprofen sodium in the drug) was calculated. The results are shown in Table 2.
[0096] Table 2 Release test results
[0097]
[0098] According to Table 2, the mixture of lecithin and polyethylene glycol-12-hydroxystearate used as a surfactant in Examples 1-3 can stably release loxoprofen sodium, while when only one surfactant is used in Comparative Examples 1-2, the release effect is significantly worse; in addition, Comparative Example 7 changes the raw material ratio, and Comparative Example 8 changes the preparation method, and the release effect is also significantly worse.
[0099] Test Example 3 In vitro skin permeation test
[0100] The modified Franz diffusion cell method was used to perform an in vitro transdermal test using the loxoprofen sodium gel patch prepared in Examples 1-3 and Comparative Examples 1-8, with pig abdominal skin as the barrier. The specific experimental method is as follows:
[0101] The cleaned pig skin was fixed to the release port of the Franz diffusion cell, and pH 7.4 phosphate buffer was added to the receiving chamber as the release medium to keep the endothelial layer in close contact with the solution. The gel patch with the cover lining removed was applied to the skin, and the water bath was adjusted to keep the temperature of the outer layer constant at (32±0.5)°C, the stirring speed was 600rpm, and 4ml of the release medium was absorbed at 0, 1h, 2h, 4h, 6h, 8h, 10h, 12h, and 24h, and an equal amount of PBS solution was added at the same time. The cumulative absorption percentage was calculated, and the results are shown in Table 3 below.
[0102] Table 3 In vitro skin permeation test results
[0103]
[0104] According to Table 3, the mixture of lecithin and polyethylene glycol-12-hydroxystearate used as a surfactant in Examples 1-3 is more conducive to the transdermal absorption effect than that in Comparative Examples 1-2; in addition, Comparative Examples 7-8 show that the raw material ratio and preparation method in the present invention also have a significant effect on the transdermal absorption effect of loxoprofen sodium.
[0105] Test Example 4 Initial Adhesion Test
[0106] The initial adhesion test was carried out according to the second method of 0952 of the fourth general rule of the Chinese Pharmacopoeia 2020 edition. The test results are shown in Table 4.
[0107] Table 4 Initial adhesion test results
[0108]
[0109] The loxoprofen sodium gel patch obtained by screening raw materials and proportioning has excellent initial adhesion and is significantly superior to commercially available products.
[0110] Test Example 5: Stability Study
[0111] The stability of the loxoprofen sodium gel patch in Example 1 and Comparative Examples 1-8 was investigated, wherein the content and related substances were determined by HPLC using a Gracesmart C column. 18 (150 mm x 4.6 mm, 5 μm), mobile phase: methanol / water / triethylamine / glacial acetic acid = 60 / 40 / 0.1 / 0.1, flow rate: 1.0 mL min -1 , detection wavelength: 222nm, column temperature: room temperature. Under the above chromatographic conditions, the chromatographic peak retention time of loxoprofen sodium is 7.1min, and the theoretical plate number is not less than 3000.
[0112] The samples were placed under strong light (illuminance 4500±500Lx) for 10 days. Samples were taken at 0, 5, and 10 days for various tests. The results are shown in Table 5.
[0113] Table 5 Stability test results
[0114]
[0115] According to the above table, when Example 1 is compared with Comparative Examples 3-4 and Comparative Example 6, it can be seen that vitamin E and ascorbyl palmitate are used together as antioxidants, and triethanolamine is added to effectively synergistically inhibit the formation of impurities and improve product stability.
[0116] Test Example 6 Evaluation of anti-inflammatory pharmacological activity
[0117] The blank control group was given 3.0 g / kg of the gel matrix; the positive control group was given 3.0 g / kg of the commercially available loxoprofen sodium gel patch (the loxoprofen sodium dose was 10 mg / kg); the experimental groups were given 3.0 g / kg of the loxoprofen sodium gel patch in Examples 1-4 and Comparative Examples 1-8 (the loxoprofen sodium dose was 10 mg / kg).
[0118] The test method is: 140 rats weighing 140-160g were randomly divided into 14 groups, and the abdomen of each rat was depilated, with the depilated area of about 2cm 2 . First, the circumference of the right hind paw of each rat was measured, and then the corresponding patch was applied to the depilatory area of each group of rats according to the group. 0.1 ml of 0.1% carrageenan was injected subcutaneously into the right hind paw of the rat 30 minutes after the patching and administration. The circumference of the right hind paw of each group of rats was measured at 1h, 2h, 4h and 6h after inflammation, and the difference before and after inflammation was used as the swelling degree. The differences in swelling degree among the groups were compared and statistically analyzed. The results are shown in Table 6.
[0119] Table 6 Swelling test results
[0120]
[0121] Note: Compared with the blank control group, P<0.05, P<0.01; compared with the Example 1 group, # P<0.05.
[0122] According to Table 6, Examples 1-4 all have excellent anti-inflammatory and detumescent effects, which are significantly different from those of the blank control group; the loxoprofen sodium gel patches in Comparative Examples 1-2 and Comparative Examples 5-8 are significantly less effective than those in Example 1.
[0123] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A loxoprofen sodium gel patch, characterized in that, The loxoprofen sodium gel patch comprises, from top to bottom, a backing layer, a drug storage layer and a protective layer; The raw materials of the drug storage layer include: loxoprofen sodium emulsion, gel matrix and pH regulator; the mass ratio of loxoprofen sodium emulsion to gel matrix is 1:5-8; The raw materials of the gel matrix include, by weight: 20-30 parts of sodium polyacrylate, 3005-10 parts of acrylic acid grafted starch, 0.5-1 parts of triethanolamine, 15-20 parts of gelatin, 0.5-5 parts of sodium edetate, 0.5-2.5 parts of a cross-linking agent, 1-5 parts of a filler, 25-35 parts of a moisturizer, 0.05-1 parts of an antibacterial agent, 0.005-1 parts of an antioxidant, and 40-50 parts of water; The cross-linking agent is selected from aluminum hydroxide; the filler is selected from silicon dioxide; the moisturizing agent is a mixture of sorbitol, hyaluronic acid and polyethylene glycol, and the mass ratio of the three is 1:0.5:1 or 1:1:1; the antibacterial agent is selected from methyl paraben; The antioxidant is a mixture of vitamin E and palmitole ascorbyl, and the mass ratio of vitamin E to palmitole ascorbyl in the antioxidant is 1:1; The raw materials of the loxoprofen sodium emulsion include, by weight: 0.5-2 parts of loxoprofen sodium, 1-2 parts of a surfactant, 3-8 parts of an organic solvent and 6-8 parts of water; The surfactant is a mixture of lecithin and polyethylene glycol-12-hydroxystearate, and the mass ratio of lecithin to polyethylene glycol-12-hydroxystearate is 1:1-2; the organic solvent is selected from diethyl adipate.
2. loxoprofen sodium gel patch according to claim 1, characterized in that, The pH regulator is one or two of L-tartaric acid, citric acid and phosphoric acid.
3. Use of the loxoprofen sodium gel patch according to any one of claims 1 to 2 in the preparation of analgesic and anti-inflammatory drugs.
Citation Information
Patent Citations
Improved cataplasm ground-mass and use thereof
CN101416955A
Loxoprofen sodium patch
CN107951866A
External preparation of flurbiprofen and preparation method thereof
CN115475152A